P158 The strength of association between the risk of endotracheal intubation and initial arterial blood (ABG) pH in patients presenting with acute hypercapnic respiratory failure (AHRF) treated with non-invasive ventilation (NIV). (16th November 2010) - Thomas, A; Beauchamp, B; Chakraborty, B; Page, M; Khanum, S; Gallagher, E; Banerjee, D; Mukherjee, R
Abstract : Introduction: The risk of failure of non-invasive ventilation (NIV) in AHRF patients is greater with higher degrees of acidosis. The BTS guidelines suggest that patients with pH <7.26 have a higher risk of NIV failure which implies a higher risk of endotracheal intubation. Aims and objectives: We set out to verify the strength of this known association of initial arterial pH (pre-commencement of NIV) and the risk of endotracheal intubation in a large dataset. Methods: A retrospective analysis of the initial ABG values on 1003 episodes of NIV at a dedicated respiratory NIV unit from 1 August 2004 to 31 December 2009. We predicted the probability of endotracheal intubation (T) using pH, pCO2 and pO2 variables, using a logistic regression model. The fitted equation was log [T/(1−T)]=53.0704–7.7064 [pH]–0.0752 [CO2 ]–0.005[O2 ] which was applied to find the strength of association and expressed as p-values. Results: In 1003 recorded episodes of acute NIV, the data entry was complete in 998 episodes on 712 unique patients. The p-values for the significance in predicting the risk of endotracheal intubation from the initial (pre-NIV) pH, CO2 and O2 are 0.0036, 0.3551, and 0.8929 respectively. The summary statistic for initial pH is stated in Abstract P158 Table 1 . Conclusion: Our survey confirms that out of initial pH, pCO2 and pO2, pH is the significant factor (p=0.0036) in predicting the risk of endotracheal intubation of acute hypercapnic respiratory failure patients treated with NIV.